2006
DOI: 10.1017/s0033291706007252
|View full text |Cite
|
Sign up to set email alerts
|

Patients with schizophrenia do not produce more false memories than controls but are more confident in them

Abstract: Although patients did not produce more false memories than controls, such errors were made with higher confidence relative to controls. The decreased confidence gap in patients is thought to stem from a gist-based recollection strategy, whereby little evidence suffices to make a strong judgment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
95
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 112 publications
(105 citation statements)
references
References 38 publications
(42 reference statements)
8
95
0
2
Order By: Relevance
“…They found that younger children made more script-related errors than older children. So, like the findings from the research using visual scenes (Moritz et al, 2006), it is likely that "real" scenes also rely on certain schemas and scripts that may influence true and false memory production.…”
Section: Spontaneous False Memories: Nontraditional Paradigmsmentioning
confidence: 86%
See 3 more Smart Citations
“…They found that younger children made more script-related errors than older children. So, like the findings from the research using visual scenes (Moritz et al, 2006), it is likely that "real" scenes also rely on certain schemas and scripts that may influence true and false memory production.…”
Section: Spontaneous False Memories: Nontraditional Paradigmsmentioning
confidence: 86%
“…A false memory paradigm containing visual scenes was used in the present study. The effectiveness of this false memory paradigm has been substantiated in previous research (Moritz et al, 2006;Peters et al, 2012). We used three black-and-white visual scenes of a classroom, funeral, and beach (see Moritz et al, 2006).…”
Section: Methodsmentioning
confidence: 93%
See 2 more Smart Citations
“…There have been a handful of studies that actually found patients to be less susceptible to false memories than controls (as reviewed in Moritz et al 2006). One theory to explain this pointed to different underlying cognitive mechanisms in patients than controls; namely, during encoding, controls may be engaging in a sustained spreading of semantic activation (Moritz et al 2004).…”
Section: Behavioral Approachesmentioning
confidence: 99%